AKUMULASI SENYAWA FENALENON PADA PISANG (Musa acuminata) YANG DIELISITASI OLEH JAMUR - Fachira Aulia Bonita, - (2020)
Panama disease and Black Sigatoka are common diseases in banana plants (Musa acuminata) caused by fungi. As a self-defense effort, plants respond by producing phytoalexin. The typical phytoalexin in the Musaceae family is phenalenone. This research aims to determine the influence of different types of fungi on the accumulation of phenalenone compounds produced by Musa acuminata and the inter-compounds relationship of phenalenone produced by Musa acuminata which is irritated by various types of fungi, as well as the possible application as fungicides. The method used is Systematic Literature Review by analyzing 13 articles that are the main reference in the study. As a result there are 37 phenalenone compounds and their derivates that are elicitate by Collectrichum musae, Fusarium oxysporum f. sp. Cubense (Foc), Mycosphaerella fijiensis, and Sporobolomyces salmonicolor fungi. Elicitation in different parts or types of fungi affects the composition and content of phenalenone compounds in M. acuminata. The biosynthesis of phenalenone compounds comes from each of the 1 phenylalanine, tyrosine, and acetate molecules intersecting phenalenones which can be associated with reactions including methylation, oxidation, adhesion, decarboxylation, and glucosylation. Understanding of the antifungal activity of phenalenone compounds is important for its use in agriculture. Keywords: Elicitor, fungi, Musa acuminata, phenalenone